U.S. educational policy and adult education: Social control; social demand; and professional adult educator participation - Phyllis M. Cunningham (Adult Education Research Conference, 1995)
Adult educators lobby for adult education legislation often without a critical analysis of its intent. Federal legislation supporting adult education has increased markedly since 1964 as a response to popular sector demands with little involvement by the adult education profession. Increasingly, the professionals’ interest has been limited to policies promoting the instrumental use of adult education often for narrow goals. This is not consistent with the democratic social agenda of many early U.S. adult educators.